Hepatitis B virus exploits C‐type lectin receptors to hijack cDC1s, cDC2s and pDCs. Issue 12 (8th December 2020) - Ouaguia, Laurissa; Dufeu‐Duchesne, Tania; Leroy, Vincent; Decaens, Thomas; Reiser, Jean‐Baptiste; Sosa Cuevas, Eleonora; Durantel, David; Valladeau‐Guilemond, Jenny; Bendriss‐Vermare, Nathalie; Chaperot, Laurence; Aspord, Caroline
Abstract: Objectives: C‐type lectin receptors (CLRs) are key receptors used by DCs to orchestrate responses to pathogens. During infections, the glycan–lectin interactions shape the virus–host interplay and viruses can subvert the function of CLRs to escape antiviral immunity. Recognition of virus/viral components and uptake by CLRs together with subsequent signalling cascades are crucial in initiating and shaping antiviral immunity, and decisive in the outcome of infection. Yet, the interaction of hepatitis B virus (HBV) with CLRs remains largely unknown. As HBV hijacks DC subsets and viral antigens harbour glycan motifs, we hypothesised that HBV may subvert DCs through CLR binding. Methods: We investigated here the pattern of CLR expression on BDCA1 + cDC2s, BDCA2 + pDCs and BDCA3 + cDC1s from both blood and liver of HBV‐infected patients and explored the ability of HBsAg to bind DC subsets through specific CLRs. Results: We highlighted for the first time that the CLR repertoire of circulating and intrahepatic cDC2s, cDC1s and pDCs was perturbed in patients with chronic HBV infection and that some CLR expression levels correlated with plasma HBsAg and HBV DNA levels. We also identified candidate CLR responsible for HBsAg binding to cDCs (CD367/DCIR/CLEC4A, CD32/FcɣRIIA) and pDCs (CD369/DECTIN1/CLEC7A, CD336/NKp44) and demonstrated that HBsAg inhibited DC functions in a CLR‐ and glycosylation‐dependent manner. Conclusion: HBV may exploit CLR pathways to hijack DC subsets and escape from immune control. Such advances bring insights into the mechanisms by which HBV subverts immunity and pave the way for developing innovative therapeutic strategies to restore an efficient immune control of the infection by manipulating the viral glycan–lectin axis. Abstract : Dendritic cells (DCs) are crucial in orchestrating immunity to pathogens. Sensing of virus/viral components and uptake by C‐type lectin receptors (CLRs) expressed by DCs initiate and shape antiviral immunity and are decisive in the outcome of infection. We demonstrate that hepatitis B virus exploits CLR pathways to hijack DC subsets and escape from immune control, paving the way for developing innovative antiviral approaches by manipulating the viral glycan–lectin axis.